Coping with Structural Change – the Regional Effects of Decentralisation in Finland - Antti Simola; Juha Honkatukia; Jouko Kinnunen; Jussi Ahokas (European Regional Science Association (ERSA), 2012)
Regional, structural change is currently among the greatest challenges facing the public sector in many EU countries at the moment. In countries like Finland, where the public sectors have a large role in providing educational, health and social services, structural change rapidly becomes a fiscal problem. Demography is directly linked to the demand for public services and to the potential growth of regional economies. On the one hand, ageing increases the demand for age-related services; on the other, it decreases labour supply, limiting the growth potential of many regions. The state's main tools for regional policies consist of both direct subsidies to the regions, as well as a mechanism reallocating tax revenues between poor and rich municipalities. However, the welfare costs of funding subsidies to poorer regions may be considerable. Thus, instruments not involving changes in spending have been preferred. Here, we consider the relocation of certain functions of the central government to the periphery – decentralization – as an instrument for coping with regional structural change. An improvement in regional municipal finances should also reduce the transfers received from the central government. This study aims at evaluating the effects of decentralization on regional development in recent years and in the near future. The study is related to an on-going evaluation of the financial relations between the central government and local authorities. Decentralization has in practice meant the relocation of central government jobs. We can cover the relocation of jobs quite accurately, and we also have the data of the number of employees that actually relocated with the jobs. Moreover, we are able to calculate state transfers to municipalities at the level of individual municipalities within each region. However, to capture all the implications of relocation to regional economies, we extend the model to take into account the average size and age profile of the families of those relocating. In this way, we obtain an estimate on the effects of decentralization on demand for public services locally, as well as on the overall effect on local population, labour supply and state, municipal and social security funds' budget balances. We analyse decentralization at the level of the twenty regions of Finland, using a dynamic, regional, AGE model. We find that while decentralisation has been beneficial for many regions by creating new jobs and increasing municipal tax revenues, it has also entailed double efforts since there is only limited obligation for the employees to relocate with the jobs. Interestingly, however, this effect is partly off-set by a reduction of transfers to municipalities.
Keywords: R13; R53; 330; regional policies; structural change